Associations of Neurocognition and Social Cognition With Brain Structure and Function in Early-Onset Schizophrenia - Guo, Pengfei; Hu, Shuwen; Jiang, Xiaolu; Zheng, Hongyu; Mo, Daming; Cao, Xiaomei; Zhu, Jiajia; Zhong, Hui (Frontiers in Psychiatry, 2022)
Background Cognitive impairment is a core feature of schizophrenia that is more serious in patients with early-onset schizophrenia (EOS). However, the neuroimaging basis of cognitive functions, including neurocognition and social cognition, remains unclear in patients with EOS. Methods Forty-three patients with EOS underwent structural and resting state functional magnetic resonance imaging scans. Brain structure and function were evaluated through the analysis of brain gray matter volume (GMV) and amplitude of low-frequency fluctuations (ALFF). They underwent comprehensive assessments for neurocognition (verbal memory, verbal expression, attention, and executive function) and social cognition (theory of mind and attributional bias). Correlation analyses were conducted to detect the potential link between cognitive function indices and brain imaging parameters. Results First, neurocognition was linked to brain structure characterized by higher immediate recall scores associated with increased GMV in the left temporal pole, higher verbal fluency scores associated with increased GMV in the left temporal pole: middle temporal gyrus, and higher Stroop-word scores associated with increased GMV in the right middle frontal gyrus. Second, social cognition was related to brain function characterized by lower sense of reality scores associated with increased ALFF in the left precentral gyrus, higher scores of accidental hostility bias associated with increased ALFF in the right middle temporal gyrus, and higher scores of accidental aggression bias associated with increased ALFF in the left precentral gyrus. Conclusion These findings may add to the existing knowledge about the cognitive function-brain relationship. They may have clinical significance for studying the mechanism of neurocognitive and social cognitive impairment in patients with EOS and providing potential neural targets for their treatment and intervention.